Pemberian Edukasi Tata Kelola Keuangan pada Kelompok Usaha Rumahan di Pondok Madina Desa Puntik Barito Kuala - Yusri Yusri; Sari Yanti; Nava Helmawanti; Ella Mauli Fatmala; Lilik Nurhidayah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Entrepreneurs in a business sometimes focus on sales and the turnover target they get. But it is also necessary to regulate the existing financial governance in a recording of transactions both incoming and outgoing in the business or business being carried out. In the conditions found, most small business actors, especially home business actors, sometimes ignore this so that when asked how the movement of cash and capital is only an estimate and cannot clearly show the track record of the transactions that have taken place. With limited knowledge and not understanding how to do a good recording process, of course, this home-based business actor cannot provide a definite picture of the data regarding profits and overall business capital. With the provision of education related to good financial governance, it is hoped that there will be an orderly system in financial management so that business continuity can be measured at the level of financial fundamentals for the short, medium and long term. Even though it is only a simple record management, of course it can describe a good history in the flow of money in and out and other expenditures. This is necessary in measuring the performance and expected targets of a business or business. Mastering accounting in financial governance is expected that the business that is run will not lose but an increase in profit. The provision of this education uses the lecture method, discussion group forums and is carried out face-to-face. A total of 15 participants took part in this activity with 5 household business activities).